"Thermal-dissolution based carbon enrichment" treatment of biomass wastes: Mechanism study of biomass pyrolysis in a highly-dispersed medium. (15th June 2021) - Hu, Zhenzhong; Li, Xian; Sun, Yiming; Donovan Dacres, Omar; Wang, Yuxian; Hu, Hongyun; Liu, Huan; Luo, Guangqian; Yao, Hong
Highlights: Pyrolysis of cellulose in a highly-dispersed and inert medium was investigated. Three distinct stages were involved in this process. The main reactions were intramolecular deoxygenation and rearrangement reactions. 86% of oxygen was removed by H2 O, CO and CO2 formations. Small molecular aromatics were formed instead of large molecular bio-char. Abstract: A novel treatment denoted as the "Thermal-dissolution based carbon enrichment (TDCE)" was proposed in our previous work to effectively deoxygenate and de-ash biomass under mild conditions. The main reactions during this process occurred in a highly-dispersed and inert medium, thus its mechanism was unclear. In this study, cellulose was chosen as the model compound to investigate the underlying reaction mechanisms of TDCE process. It was confirmed that three distinct stages were involved in this process, which were physical dissolution stage, intramolecular deoxygenation and rearrangement stage, and stabilization stage. The deoxygenation attributed to the intramolecular dehydration at around 300 °C and the formations of CO2 and CO through subsequent aromatization in liquid phase at around 350 °C. Around 67% and 19% of oxygen were removed by these two pathways, respectively. About 80% of carbon remained in the solid products in all conditions. A two-step process was verified for the aromatic substance formation: furan structure formation at the beginning and the subsequent conversion to benzene ring. Especially, unlike large molecular bio-char formation in conventional pyrolysis, small molecular aromatics were formed in TDCE process. Undoubtedly, the highly-dispersed and inert medium contributed to these intramolecular reactions and suppressed the intermolecular reactions, although it wasn't involved in the chemical reactions. Hence, the unique reaction mechanism of biomass in a highly-dispersed medium was specified, providing theoretical guidance to the practical application of TDCE method.